Valor económico agregado y el precio-beneficio de la acción en empresas de la Bolsa de Valores de Lima. 2008 – 2017 - Cuyate Reque, Pedro Jesus (2020)
ABSTRACT One of the existing investment alternatives is the stock market; and in Peru the Lima Stock Exchange (BVL) is responsible for allowing the exchange of securities traded on this market. Despite the increased uncertainty in the investment of companies listed in the BVL, it is noted that there are companies with high-priced frequencies, forming a liquid market, yet it is necessary to mitigate these uncertainty and generate security when taking an investment decision, which is why the main objective of the present research was to analyze the ratio of the added economic value (EVA) and the share benefit price (PER) of the companies that trade in the BVL with the most frequently traded in 2008-2017; a quantitative approach was used, with an applied level of the correlational type, using documentary analysis in the selected companies as a study sample; concluding that Telefónica del Perú had the degree of correlation with greater intensity being directly proportional; then of Casagrande with a moderately proportional correlation, and finally Volcan Compañía Minera and Refinery la Pampilla which obtained a directly proportional weak correlation.